Bumps in the Road : Challenges to E-bus Implementation - Graham, John (International Finance Corporation, Washington, DC, 2020)
Dozens of municipalities are experimenting with e-buses, while some last-mile delivery companies are using pilot fleets to test performance. At the same time, a smaller group of operators are pushing ahead with more drastic, big bang efforts to put dozens or even hundreds of electric vehicles into service. The authors saw how some locations have already reached total cost of ownership (TCO) parity, while other places will require further reductions in costs and perhaps some forward-thinking tax and tariff policies. The bad news is that the track record for electric buses to date has been mixed, and e-bus adoption has not scaled up as fast as many had hoped due to institutional, technical, and financial challenges. For those seeking to stay the course with internal combustion engines, there are plenty of valid arguments. This report will bring some of the problems out in the open.